Barriers and enablers: How logistics companies could tackle the transition to electrified road freight transport - Henrik Gillström (Cleaner Logistics and Supply Chain)
Electrifying road freight transport can heavily reduce the sector’s climate impact; however, there exist many uncertainties for making a large-scale transition, especially for logistics companies. In response, the purpose of this article is to identify and describe barriers to transition, but also strategies for how the barriers can be managed. To address the purpose, an interview study was carried out together with two complementary workshops to capture the views of relevant actors. Barriers to electrification are clustered into four separate areas: practical and technological barriers, financial barriers, institutional barriers, and social and cultural barriers. Low cost and high logistics performance are viewed as logistics companies’ competitive advantages, but they are expected to be challenged when making the transition. The current structure of the transport chain also further complicates things: it is transaction-based and risks and benefits can occur in its different parts. This is an issue, since the actor that is forced to take risks is not always the actor that benefits the most. One way to manage this is for actors to form more long-term commitments through collaborations. Moreover, it can be advantageous to start electrifying subsystems that can be described as ‘closed’ and ‘static’, i.e. predictable and easy to control, such as transport between terminals. At the other end of the spectrum, subsystems that are ‘open’ and ‘dynamic’ are the ones that are most difficult to electrify.